The Impact of Corporate Governance on Market Capitalization: Evidence from Listed Firms of DSE - Uddin, MD. Hasan (International Journal of Economic, Finance and Business Statistics, 2024)
This study examines the relationship between the corporate governance (CG) mechanisms related to board size (BS), board independence (BI), board committees (BC), ownership structure (OS), and the market capitalization of companies listed in the Dhaka stock exchange (DSE). Secondary data from 41 listed firms in Dhaka Stock Exchange during the period of 2015 to 2022 is utilized in this study. The ordinary least square, regression techniques were applied on the panel data collated to estimate the model. The findings reveal a significant positive impact of board committees and board independence on the market capitalization of the companies, while ownership structure shows a significant negative effect on the market capitalization of the companies. This finding supports the hypothesis that corporate governance adds value to companies and that investments in effective governance systems have a net positive benefit and should be pursued.